Sequential Optimization Configuration Method for Power Quality Monitors Considering Photovoltaic Access - Xiaorui Liang; Qiming Zhong; Huaying Zhang; Ying Wang; Huicong Liu (IEEE Access)
With the increasing demand for sensitive load and the large-scale integration of photovoltaic (PV) power sources, the monitoring of voltage sag in new power systems has encountered new challenges. Some literature has studied the optimization configuration method of power quality monitor (PQM), which ensures the observation performance of the configuration scheme while minimizing investment costs. Although some papers have studied the configuration issues of PQM, there are still some problems in the application of existing methods in new distribution systems, such as the need to propose a method for calculating the amplitude of voltage sag under PV access, the impact of PV output volatility on the monitoring range of PQM has not been discussed, and there is still a research gap in optimizing configuration methods that consider the continuity of PQM configuration. This article aims to address the three issues mentioned above. Firstly, the improved k-means algorithm is used to reduce PV output scenarios and a calculation method for the amplitude of voltage sag considering PV access is proposed. Secondly, a dynamic observability matrix construction method is proposed to characterize the impact of PV output fluctuations on PQM monitoring. Finally, an optimized configuration model is constructed considering the continuity of PQM configuration. The IEEE-69 node system was used to validate the method proposed in this paper. Simulation results show that the average composite observability index of the configuration scheme in this paper is 0.0284 smaller than that of the traditional scheme and the average cost saving RMB2593.75. This demonstrates the proposed method can effectively improve the monitoring performance of the new distribution network, while reducing the additional costs caused by discontinuous configurations. Finally, the optimal configuration method of multi-type measurement devices will be the focus of future research.